The Love Trap. Romanticization practices of the Italian generations of the 90s - Fulvio Cozza (Archivio Antropologico Mediterraneo)
Drawing from material collected during two ethnographic investigations conducted in Rome and Lazio, I will focus on the experience of love triggered by relationships with human beings and archaeological remains. I aim to show how these activities give rise to a romantic experience in a context that paradoxically regards love as a fictional and unreliable reality. Utilizing Ernesto De Martino’s conceptual framework, I describe that for the transitional generation born around 1990, caught between precariousness and the triumphant narratives of their predecessors, romantic discourse serves as a shield against existential annihilation by the uncontrollable forces of the universe. It also serves as a means to attain a distinctive identity validated by Italian tradition and heritage. However, while love offers a stable and trustworthy refuge, it can also render individuals powerless to change their life situation and cope with a lack of future prospects.